Pengaruh Book Tax Differences, Kepemilikan Manajerial, Dan Leverage Terhadap Persistensi Laba: Studi Perusahaan Property Dan Real Estate di Bei Tahun 2020 – 2023 - Meylan Adisti Ridwan Tika; Destia Pentiana; Rusmianto Rusmianto (AKUNTANSI 45, 2025)
This study aims to examine the influence of Book tax differences, managerial ownership, and leverage on earnings persistence in companies. Using a quantitative approach with multiple linear regression analysis, this research processes financial statement data to test the relationships between these variables. The findings reveal that Book tax differences and managerial ownership have a negative impact on earnings persistence. This indicates that the greater the disparity between financial accounting and taxation, as well as the higher the proportion of shares owned by managers, the lower the company's earnings sustainability. Meanwhile, leverage does not have a significant effect on earnings persistence, suggesting that a company's debt level does not determine long-term earnings stability. These findings align with agency theory, which highlights conflicts of interest between managers and shareholders, as well as signaling theory, which emphasizes the importance of financial information in assessing a company's performance.